Home Bias, Foreign Mutual Fund Holdings, and the Voluntary Adoption of International Accounting Standards - COVRIG, VICENTIU M.; DEFOND, MARK L.; HUNG, MINGYI (Journal of Accounting Research, 2007)
ABSTRACT We test the assertion that a consequence of voluntarily adopting International Accounting Standards (IAS) is the enhanced ability to attract foreign capital. Using a unique database that reports firm‐level holdings of over 25,000 mutual funds from around the world, our multivariate tests find that average foreign mutual fund ownership is significantly higher among IAS adopters. We also find that IAS adopters in poorer information environments and with lower visibility have higher levels of foreign investment, consistent with firms using IAS adoption to provide more information and/or information in a more familiar form to foreign investors. Taken together, our findings are consistent with voluntary IAS adoption reducing home bias among foreign investors and thereby improving capital allocation efficiency.